How Important is Wealth for Explaining Household Consumption Over the Recent Crisis? An Empirical Study for the United States, Japan and the Euro Area - Kerdrain, Clovis (OECD Economics Department Working Papers, 2011)
This paper provides new empirical results linking financial and housing wealth to household consumption for the United States, Japan and the euro area. The results suggest that there are important cross-country differences in how wealth, especially housing wealth, affects consumption. They further demonstrate that it can be important to take into account wealth effects on consumption in short-term forecasting exercises, a point which is particularly well illustrated in relation to the recent economic crisis. In addition, conditional projections underline the importance of asset price developments and wealth in determining US savings over the medium term